A Preliminary Note on Physical and Mechanical Properties of Borassus flabellifer (Palmyra) from Andhra Pradesh - Sekhar, A. C.; Rajput, S. S.; Dangwal, M. N. (Indian Forester, 1968)
0.1. Physical and mechanical tests were done in green and kiln-dry conditions on standard small clear specimens of Borassus flabellifer (Palmyra), received from Visakhapatnam North Division, Andrha Pradesh. The results have been presented and discussed.